The defining role of interface crystallography in corrosion of a two-phase pearlitic steel. Issue 11 (2nd June 2020) - Khan, M.I.; Mehtani, H.K.; Durgaprasad, A.; Goyal, G.K.; Prasad, M.J.N.V.; Parida, S.; Dasgupta, T.; Birbilis, N.; Samajdar, I.
ABSTRACT: This study involved thermomechanically processed fine (few hundred nanometers of interlamellar spacing) pearlite wire rods of the different axial alignment of the pearlite colonies, and coarse (several micron interlamellar spacing) pearlite colonies. In the former, appropriate microstructural tailoring, and corresponding axial alignment, reduced the corrosion rate, in chloride solution, by nearly 6.4 times. In the coarse pearlite, on the other hand, dissolution and aqueous corrosion, influenced by microgalvanic coupling, was shown to be restricted to the ferrite side of the ferrite-cementite interface. The orientation relationship between ferrite and cementite determined localised corrosion. In summary, remarkable improvements in the resistance to galvanic corrosion were shown, in coarse two-phase pearlite, by enhancing the population of good-fit interfaces. Though the same observation was not possible, experimentally, in the fine pearlite colonies, the remarkable improvement in the corrosion resistance of aligned pearlite wire rods appears real and extremely reproducible.